VAAFT PROCEDURE (Video-assisted Anal Fistula Treatment) versus Open Method in the Treatment of High Fistula in Ano - Kadhim, Asaad Mohammed; Altaraikhim, Madhi Hashim Otaiwi (Journal of Coloproctology, 2022)
Background A common acquired anorectal condition is anal fistula. The treatment approaches that have been employed have been linked to erratic outcomes and sometimes life-threatening consequences. Video-assisted anal fistula treatment (VAAFT), a minimally invasive method, was introduced for adult patients in 2011.Objective To know the efficacy of the VAAFT procedure in treating high anal fistulas and to compare it to open methods in the Basrah province.Methods The present study was performed on 200 patients with high fistulas in ano in Basrah province. We divided the patients into 2 groups: Group A: treated by the VAAFT technique and Group B: treated by open fistulotomyResults The patients treated with VAFFT revealed no occurrence of the following postoperative complication: Infection, incontinence, recurrence, anal stenosis, and bleeding. There was lower incidence of pain, short time for wound healing, rapid return to work, and more patient satisfaction compared with open fistulotomyConclusion An innovative method for managing ano fistula is VAAFT. Compared with traditional methods, it has a lot of benefits. It is day case surgeryno open wound.no damage to anal sphincter and no risk of incontinence, it is more affordable.it allow for clear identification of internal office, whole tract and its associated branches and cavity. The instrument can be used for multiple patients after good sterilization and disinfection.
Keywords: anal fistula; VAAFT; minimally invasive approach